Revisiting the incomplete Mary - Raymond Potgieter (In die Skriflig, 2020)
It has taken two millennia to arrive at the Roman Catholic Church’s Mary – a figure similar but distinct from the biblical account of Mary. Early Christian Church history attests that Mary was accorded titles which did not reflect in the New Testament. These titles served to buttress the historical and present day claims made among the Roman Catholic Church’s faithful. The most influential title for Mary accepted by the Christian Church was that of Theotokos. For classical theology, this title affirmed and sharpened the definition of the undivided divinity and humanity of Mary’s Son, Jesus. In due time, this title served to support the addition of numerous other Catholic titles for Mary such Mother of the Church, queen of heaven, and more. Consequently, traditional theology began to accommodate the inclusion of Mariology in its taxonomy. This was necessary to address assumptions and claims such as Mary’s continual virginity, assumption into heaven and mediating role(s). While Mariology depicts Catholic doctrine, it is not defined by the Magisterium. That means that it cannot be finally accepted as divinely revealed and infallibly defined. For that reason, this article suggests that the Mary of the Catholic Church is still a figure in the making in stark contrast to the Mary of the Bible and classical Protestant theology and Reformed Christian faith.